2001
DOI: 10.1089/08977150150502587
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependency of45Calcium Accumulation Following Lateral Fluid Percussion: Acute and Delayed Patterns

Abstract: This study was designed to determine the regional and temporal profile of 45calcium (45Ca2+) accumulation following mild lateral fluid percussion (LFP) injury and how this profile differs when traumatic brain injury occurs early in life. Thirty-six postnatal day (P) 17, thirty-four P28, and 17 adult rats were subjected to a mild (approximately 2.75 atm) LFP or sham injury and processed for 45Ca2+ autoradiography immediately, 6 h, and 1, 2, 4, 7, and 14 days after injury. Optical densities were measured bilater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
81
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(87 citation statements)
references
References 84 publications
6
81
0
Order By: Relevance
“…There are numerous possible mechanisms that may explain this depression including disruption of mitochondrial metabolism by calcium accumulation (Fineman et al, 1993;Osteen et al, 2001), ionic flux disruptions (Katayama et al, 1990), reduced cerebral blood flow (Cherian et al, 2004), or lactic acid accumulation (Kawamata et al, 1995). Another consideration is that following the initial surge in neurotransmitter release and ionic fluctuations the brain activity may become quiescent and therefore require less substrate.…”
Section: Age Differences In Cmrglc After Tbimentioning
confidence: 99%
“…There are numerous possible mechanisms that may explain this depression including disruption of mitochondrial metabolism by calcium accumulation (Fineman et al, 1993;Osteen et al, 2001), ionic flux disruptions (Katayama et al, 1990), reduced cerebral blood flow (Cherian et al, 2004), or lactic acid accumulation (Kawamata et al, 1995). Another consideration is that following the initial surge in neurotransmitter release and ionic fluctuations the brain activity may become quiescent and therefore require less substrate.…”
Section: Age Differences In Cmrglc After Tbimentioning
confidence: 99%
“…Different motivational factors are involved in forced exercise compared to voluntary exercise (Leasure and Jones, 2008); thus it is predicted that the stress response will also differ. We utilized the fluid percussion injury (FPI) model for these studies, a type of TBI that in our hands results in no gross neuronal death (Gurkoff et al, 2006;Osteen et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…3,[8][9][10][11][12][13][14][15][16][17][18][19] During the first four years of life, numerous cerebral developmental changes occur, which may contribute to these differences within the pediatric population, including continued myelination, changes in cerebrovascular tone, and increases in both brain size and neurotransmitter density. [20][21][22] Experimental studies of the age-dependent response to a scaled cortical impact found larger lesion volumes at seven days and one month post-TBI in four-week-old piglets, compared with five-dayold piglets.…”
mentioning
confidence: 99%